Display Instagram @starbucksIndonesia : Stimulus Masyarakat Konsumsi Pada Gerai Starbucks Central Park Mall - Meisy Efna Prisylia (LPPM Stikosa - AWS, 2020)
This research sees social media Instagram @Starbucks inndonesia as a display in attracting people to buy products. The theory used in this research is the Consumption Society theory put forward by Baudrillard. The method used is an interpretative qualitative research method with Baudrillard's post-modern approach. Data collection was carried out with literature studies and text observations on Starbucks Indonesia Instagram social media. The results showed that our society has now become a consumptive society with the internet as a new medium for delivering messages, especially displays that attract customers' attention. With the development of new media, the activities of our society are now closely related to social media, especially Instagram, which currently has more than 61 million active users by the end of November 2019. People who follow Instagram Indonesia Instagram accounts can get the information provided and interested and want to buy products that are being offered especially in certain seasons.